The Black Box - Connelly, Michael 1956-; McConnohie, Michael (New York : Hachette Audio, 2012)
Harry Bosch investigates after a bullet from a recent killing is a match for one used in the unsolved murder of a photographer in 1992.
Unabridged.
Compact discs.
Read by Michael McConnohie.
Keywords: Bosch, Harry (Fictitious character) -- Fiction; Police -- Fiction -- California; Women photographers -- Fiction -- Crimes against; Cold cases (Criminal investigation) -- Fiction; Murder -- Fiction -- Investigation; Los Angeles (Calif.) -- Fiction; Mystery fiction; Audiobooks